The Influence of Human Resource Competence and the Use of Information Technology on the Quality of BUMDES Financial Reports - Rahayu, Peti Sri; Sudrajat, Sudrajat; Alvia, Liza (Basecamp Economics PubMed, 2024)
This research aims to empirically prove the influence of human resource competence and the use of information technology on the quality of financial reports. The population in this study were all BUMDes supervisors in Lampung province totaling 212 BUMDes units. The sample for this research was 138 people who supervise BUMDes. This research method uses quantitative methods. The data analysis technique for this research uses multiple linear regression analysis and analysis tools using SPSS 25. The results of human resource competency and the use of information technology partially influence the quality of BUMDes finansial.